PENGARUH DISPOSISI MATEMATIS TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA SMP - Apri Kurniawan; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study aims to determine the extent to which mathematical disposition affect the problem solving abilities. The method used is quantitative descriptive with correlation technique. The population in this study were all 8th grade Junior High School students in Cilacap district with a sample of 31 students who were selected purposively at one Junior High School. Data obtained by testing the problem solving tes instrumen as many as 5 questions then analyzed the achievement on each indicator of ability and non tes in the form of a mathematical disposition questionnaire of 25 statements. The research data were processed using SPSS 16.0 software by conducting pearson correlation tes and the results were analyzed descriptively. The results of the study concluded that there was a moderate positive correlation between mathematical disposition of problem solving abilities with a correlation of 0,556 and a coefficient of determination of 0,309 at a significance of 0,05. This shows that the higher the mathematical disposition, the higher the problem solving ability of students with an effect of 30,9%